Analisis Yuridis Perjanjian Kredit Pemilikan Rumah Program FLPP dalam Perspektif Keadilan Kontraktual - Irvan Ravi Rowa; Lukman (Peradaban Journal of Law and Society, 2026)
The Housing Financing Liquidity Facility (FLPP) program is a government initiative designed to expand access to homeownership for low-income households through mortgage financing. In its implementation, the legal relationship between banks and debtors requires not only legal certainty but also contractual justice, particularly because the use of standard-form contracts may create an imbalance in the parties' bargaining positions. This study aims to analyze the implementation of mortgage agreements under the FLPP program from the perspective of contractual justice. It employs an empirical juridical approach using a qualitative descriptive method. Data were collected through interviews with 20 informants, consisting of bank personnel and debtors, and were complemented by observation and document analysis. The findings reveal that, although mortgage agreements formally comply with the requirements of Indonesian contract law, the use of standard-form contracts continues to create an unequal bargaining position between banks and debtors. This finding demonstrates that the formal validity of a contract does not necessarily ensure contractual justice. The study further shows that the resolution of non-performing loans primarily relies on debt restructuring as a non-litigation mechanism, while litigation is considered a measure of last resort. These findings underscore the importance of enhancing contractual transparency, ensuring a balanced allocation of rights and obligations between the parties, and strengthening loan resolution mechanisms based on the principle of contractual justice. Program Fasilitas Likuiditas Pembiayaan Perumahan (FLPP) merupakan instrumen pemerintah untuk memperluas akses kepemilikan rumah bagi masyarakat berpenghasilan rendah melalui pembiayaan Kredit Pemilikan Rumah (KPR). Dalam pelaksanaannya, hubungan hukum antara bank dan debitur tidak hanya menuntut kepastian hukum, tetapi juga keadilan kontraktual, terutama karena penggunaan kontrak baku berpotensi menimbulkan ketidakseimbangan posisi tawar. Penelitian ini bertujuan menganalisis pelaksanaan perjanjian KPR melalui Program FLPP dalam perspektif keadilan kontraktual. Penelitian menggunakan pendekatan yuridis empiris dengan metode deskriptif kualitatif. Data diperoleh melalui wawancara terhadap 20 informan yang terdiri atas pihak internal bank dan debitur, serta didukung observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa secara formal perjanjian kredit telah memenuhi ketentuan hukum perjanjian, namun penggunaan kontrak baku masih menimbulkan ketidakseimbangan posisi tawar antara bank dan debitur. Temuan ini menunjukkan bahwa keabsahan formal perjanjian belum dengan sendirinya mencerminkan keadilan kontraktual. Penelitian juga menunjukkan bahwa penyelesaian kredit bermasalah lebih mengedepankan restrukturisasi dibandingkan litigasi sebagai mekanisme penyelesaian sengketa. Temuan tersebut menegaskan pentingnya transparansi kontrak, keseimbangan hak dan kewajiban para pihak, serta mekanisme penyelesaian kredit yang berorientasi pada prinsip keadilan kontraktual.